Cloning, expression, purification, characterization, crystallization and X‐ray crystallographic analysis of recombinant Der f 21 (rDer f 21) from Dermatophagoides farinae. Issue 11 (1st November 2015) - Pang, Sze Lei; Ho, Kok Lian; Waterman, Jitka; Teh, Aik‐Hong; Chew, Fook Tim; Ng, Chyan Leong
Abstract : Dermatophagoides farinae is one of the major house dust mite (HDM) species that cause allergic diseases. N‐terminally His‐tagged recombinant Der f 21 (rDer f 21), a group 21 allergen, with the signal peptide truncated was successfully overexpressed in an Escherichia coli expression system. The purified rDer f 21 protein was initially crystallized using the sitting‐drop vapour‐diffusion method. Well diffracting protein crystals were obtained after optimization of the crystallization conditions using the hanging‐drop vapour‐diffusion method with a reservoir solution consisting of 0.19  M Tris–HCl pH 8.0, 32% PEG 400 at 293 K. X‐ray diffraction data were collected to 1.49 Å resolution using an in‐house X‐ray source. The crystal belonged to the C ‐centered monoclinic space group C 2, with unit‐cell parameters a = 123.46, b = 27.71, c = 90.25 Å, β = 125.84°. The calculated Matthews coefficient ( V M ) of 2.06 Å 3  Da −1 suggests that there are two molecules per asymmetric unit, with a solvent content of 40.3%. Despite sharing high sequence identity with Blo t 5 (45%) and Blo t 21 (41%), both of which were determined to be monomeric in solution, size‐exclusion chromatography, static light scattering and self‐rotation function analysis indicate that rDer f 21 is likely to be a dimeric protein.